Revision of the National Forest Policy - Sagreiya, K. P. (Indian Forester, 1978)
Since the enunciation, soon after independence, of the National Forest Policy in 1952, many changes of far reaching consequence have taken place in the country, in the social and the economic field, which necessitate restatement of this Policy. The area under forest has progressively shrank. Had the sagacious counsel of the 1952 policy been heeded and adequate Treelands and Fuel-cum-Fodder Reserves created, and grazing in the forest controlled, we would have solved to a great extent, the vexed problem of Nistar and saved the accessible forests from depletion. The best solution for meeting the changed circumstances, and yet safeguarding the future, is to exploit the existing depleted forests of inferior, slow-growing trees, as early as feasible, and then to fully restock the felled over area with superior, faster growing trees before the ecological conditions deteriorate, and thereafter to protect and tend the crops thus obtained till their financial maturity. The revised policy should also lay down that research should be intensified, better amenities provided to the forest personnel and people made forest-conscious by audio-visual propaganda.